Modeling Travel Distance to the Nearest Mosque Using the Euclidean Distance Algorithm - Dicky Dharmawan; Mikha Sinaga; Nita Sembiring (Journal of Intelligent Computing and Advanced Data Science, 2026)
The study will calculate the travel distance to the closest mosque through the Euclidean Distance formula, which is a standard formula for the straight-line distance between two geographic points. The overall goal is to calculate the accessibility of mosques within an area by using geographical coordinates and provide valuable data for city planning and religious facility planning. Applying the Euclidean Distance formula, studies estimate closeness between given set of points and nearest mosque and thus is a straightforward yet efficient way to quantify closeness. Findings from research indicate high variability in mosque accessibility based on geographical distribution in the study area. The model indicates areas with inadequate mosque access, and it may be utilized by planners and policymakers in responding to the need for enhanced religious service coverage. The Euclidean Distance model is limited in the sense that it does not account for actual conditions such as the road network, traffic, or terrain that may influence actual travel distance and time. This research contributes to the existing literature in spatial analysis by demonstrating how the Euclidean Distance algorithm can be applied in geographic research on access to public services. More advanced algorithms and actual data sets can be employed by future researchers to continue enhancing the precision and applicability of the model in actual environments.